Financial Performance Improvement Influenced By Good Corporate Governance Through Company Value - Rika Lidyah; Muhamad Risal Tawil; Siti Aisyah; Hardiansyah, Hardiansyah; Wirman, Wirman (Sharia Journal and Education Center Publishing, 2025)
This research is a quantitative study with an explanatory approach, namely an approach that generates hypotheses based on hypotheses in previous studies. The data used in this study are primary data that researchers obtained from 300 Sinarmas employees spread throughout Indonesia. The data obtained were collected and analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the Good Corporate Governance variable can have a positive relationship direction and a significant influence on Company Performance. The results of the third table above show that the better the Good Corporate Governance owned by a company can increase employee welfare, improve the company's financial stability, and ultimately improve Company Performance. These results are because the company's P-Values ​​value is below the significance level of 0.05, which is 0.000. In the next column, the P-Values ​​value in this article can also be said to be proven because the same thing is that the P-Values ​​value is below the significance level of 0.05, which is 0.000 smaller than direct testing. Thus, it can be concluded that the Company Value variable can moderate the influence of the Good Corporate Governance variable on Company Performance.